Studi Empiris Tentang Living Hadis Tholabul ‘Ilmi Di Mi Tahfidz Al-Fathimiyah: Dampak Dan Implikasinya - Sihono Sihono; Moh Faliqul Isbah (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
This study explores the implementation of the Tholabul ‘Ilmi Hadith at MI Tahfidz Al-Fathimiyah and its impact on Islamic education. The research aims to understand how the Tholabul ‘Ilmi Hadith is applied in daily life at the institution and its implications for the educational process. A qualitative research method was used, collecting data through observation, interviews, and document analysis. The findings indicate that the integration of Tholabul ‘Ilmi in the curriculum of MI Tahfidz Al-Fathimiyah not only enhances students' religious knowledge but also contributes to their character formation. This study contributes by offering a model for implementing Hadith-based Islamic education that is both adaptive and relevant, providing a reference for curriculum development in other Islamic educational institutions.